Content Analysis of Merdeka Curriculum-Based Teaching Modules in Students' Character Building Values - Nur Arumsari; Astiyandha, Tauricha; Tamela, Ellis (Universitas Islam Lamongan, 2025)
Characters education is crucial in Indonesian pedagogy to address the challenges of the 21st century, evidenced by Ministry of National Education and Culture attempts to promote character-building values in academic documents in different curriculums. Previous research has examined character values in lesson plans, syllabus, textbooks in the 2013 curriculum, and even media such as songs and movies or other literary works. However, no research has analyzed character values in teaching modules within Merdeka Curriculum. This study investigates character building values in five English language teaching modules created by student teachers, using by Ministry of National Education and Culture of character indicators which were derived from five of character building values at the stage of teaching (pre, core and post-teaching). A qualitative content analysis of the findings revealed that responsibility (42%) appeared most frequently, followed by communicative (25%), Hard Work (19%), Religious (11%), while nationalism (3%) was least represented. This result indicates that the character values in the teaching module are aligned of the national education policy, so it is worthy of review for all educators, especially for student teachers to be well-prepared and competent in designing character-based teaching modules for English learning at the high school level to build students' competencies that are intact academically and character-wise.